Estudo de liquens corticícolas foliosos em um mosaico de vegetação no sul do Brasil - Käffer, Márcia Isabel (Universidade do Vale do Rio do Sinos, 2005)
Lichens are important epiphytic components of forests, however anthropogenic alterations of forest habitats could lead to substantial modifications in the diversity and species spatial distribution of lichens. This work investigates how species composition, richness, abundance, diversity and vertical distribution of lichens in tree trunks could be modified when native forest is replaced by forest monocultures. The lichen community was studied in the National Forest of São Francisco de Paula, southern Brazil, in three replicates of the following vegetation types: native Araucaria forest, and plantations of Araucaria, Pinus and Eucalyptus, 12 areas in total. In each area, ten host-trees were randomly chosen, with a total of 120 host-trees sampled in the four habitats. In each host –tree, lichens were surveyed from 30 to 150 cm in trunk height. There were 113 lichen species registered, 78 in the survey and 35 in an additional non systematic survey. Five new species to science were encountered, eight new citation
lichens;forest;Araucaria angustifolia
Keywords: araucária angustifolia; florestas nativas; liquens corticícolas foliosos; Ciências Biológicas